Instagram sebagai Ruang Politik Digital Mahasiswa: Analisis Filsafat Politik dan Relevansinya terhadap Pendidikan Islam - Ayu Gintari; Afifuddin Harisah; Andi Marjuni (Aksioreligia, 2026)
The rapid growth of social media has transformed political communication among young people, making Instagram an important digital political space for accessing information, expressing opinions, and participating in democratic processes. This study aims to analyze the use of Instagram as a digital political space among students of the Faculty of Teacher Training and Education, Tanjungpura University, through the lens of political philosophy and to examine its relevance to Islamic Education. This study employed a descriptive qualitative approach. Data were collected through semi-structured interviews and document analysis and analyzed using thematic analysis. The findings indicate that Instagram functions as a digital public sphere that facilitates political information, discussion, and participation. Students perceive freedom of expression as a right accompanied by responsibility, verify political information before sharing it, and recognize the influence of algorithms in shaping political perceptions. The findings are relevant to Islamic Education by reinforcing the values of tabayyun (verification), ṣidq (truthfulness), amānah (trustworthiness), shūrā (deliberation), and al-'adl (justice) as ethical principles for political communication in digital spaces. These findings contribute to strengthening political literacy, digital literacy, and ethical citizenship within the context of Islamic Education.